Amniotic membrane promotes doxorubicin potency by suppressing SH-SY5Y neuroblastoma cell angiogenesis - Ahmed M. Abou-Shanab; Shaimaa Shouman; Alaa E. Hussein; Ola A. Gaser; Shireen Magdy; Eman Ashraf; Radwa Ayman Salah; Omaima Idris; Nagwa El-Badri (BMC Cancer)
Abstract Background Doxorubicin (DOX) remains a mainstay for neuroblastoma (NB) treatment, but side effects hamper efficacy. We previously showed that DOX induces SH-SY5Y NB cell angiogenesis via the PHD-2/HIF-1α axis. Adjuvant therapies offer a promising avenue to improved outcomes. Human amniotic membrane (hAM) extract (hAME) consists of various proteins that exhibit anti-cancer and anti-angiogenic properties. This study investigates hAME as a potential adjuvant for targeting NB angiogenesis when combined with DOX. Methods We used cellular, molecular, and biochemical assays to evaluate the antitumorigenic activities of hAME + DOX (D + E) treatment across key hallmarks of SH-SY5Y NB progression: proliferation, cell cycle, angiogenesis, invasiveness, differentiation, and cellular bioenergetics. Results D + E treatment significantly suppressed SH-SY5Y cell proliferation, induced cell cycle perturbations, and reduced viability, while protecting bone marrow stem cells and human skin fibroblast normal cells. D + E treatment also countered SH-SY5Y cell invasiveness and promoted a favorable mesenchymal-to-epithelial transition (MET). Importantly, D + E treatment modulated the SH-SY5Y cellular respiration, evidenced by halted glycolytic metabolism, potentially influencing a shift towards oxidative phosphorylation and boosted urea cycle progression. Mechanistically, D + E abrogated DOX's pro-angiogenic effects and inhibited SH-SY5Y cells’ neo-vascularization in a chick embryo model. Conclusions These findings suggest hAME as a promising adjuvant therapy for NB, potentially offering an effective and safe treatment strategy by targeting multiple hallmarks of NB. Graphical Abstract